Acute physiological and perceptual responses to a netball specific training session in professional female netball players - LAURENCE BIRDSEY (PLOS ONE, 2022)
The 24 h responses to professional female netball-specific training were examined. British Superleague players (n=14) undertook a 90-min on-court training session incorporating key movement, technical, and scenario-specific match-play drills. Perceptual (mood, fatigue, soreness), neuromuscular (countermovement jump peak power output [PPO], PPO relative to mass [PPOrel], jump height [JH]), endocrine (salivary cortisol [C], testosterone [T] concentrations) and biochemical (creatine kinase concentrations [CK]) markers were assessed at baseline (immediately before; Pre), and immediately, two and 24 hours after (+0h, +2h, +24h) training. Session (sRPE) and differential (dRPE) ratings of perceived exertion were recorded at +0h. Identification of clear between time-point differences were based on the 95% confidence interval (CI) for mean differences relative to baseline values not overlapping. At +0h, C (raw unit mean difference from baseline; 95% CI: 0.16; 0.06 to 0.25 μg·dl-1), T (32; 20 to 45 pg⋅ml–1), CK (39; 28 to 50 u·L-1), PPOrel (2.4; 0.9 to 3.9 W·kg-1) and PPO (169; 52 to 286 W) increased. At +2h, fatigue (15; 7 to 24 AU), CK (49; 38 to 60 u·L-1), and soreness (14; 3 to 25 AU) increased, while T (- 24; -37 to -11 pg⋅ml–1) and mood (-20; -27 to -12 AU) reduced. At +24h, CK increased (25; 13 to 36 u·L-1) whereas PPOrel (-1.6; -3.2 to -0.1 W·kg-1) and JH (-0.02; -0.03 to -0.08 m) reduced. Responses were variable specific, and recovery of all variables did not occur within 24h. The residual effects of the prior stimulus should be accounted for in the planning of training for professional female netball players.